The Effect of Silicone Tube and Silicone Tube plus Hyaluronic Acid Application on Adhesion Formation in Experimental Peri- and Epi-neurorrhaphy in A Rat Model - Ozaydin, Isa; Unsaldi, Emine; Aksoy, Ozgur; Yayla, Sadik; Kaya, Miktat; Ulkay Tunali, Muzaffer Basak; Erdogan, Hakan (Kafkas Univ, Veteriner Fakultesi Dergisi, 2014)
Following neurorrhaphy in Wistar albino rats with experimental sciatic nerve cut, the effectiveness of solely silicone tube (ST) and ST plus hyaluronic acid application on preventing fibrosis was clinically and histopathologically examined. After a total nerve cut is created in sciatic nerve, interfascicular and epineural anastomosis was used. While only anastomosis was applied for the first group (Control Group), for the second group (ST Group) anastomosis + silicone tube and for the third group (ST + HA Group) anastomosis + silicone tube + hyaluronic acid (HA) were applied. Animals in each group were divided into 2 sub-groups and macroscopic and histopathological examinations were conducted on the 30th and 60th postoperative day. On day 30 of the study all the animals had problematic walks. On the 60th day while animals in groups ST and ST + HA were walking normally, the problem was still going on for the control group. In the postmortem macroscopic examinations performed in the control group on the 30th and 60th days an irregular morphology and adhesion to surrounding in nerve tissue were seen. Whereas in group ST, in the anastomosis line within the tube, scar tissue which was clearer on the 60th day was observed, in group ST + HA it was seen that nerve anastomosis line was smooth on the 30th and 60th days. As a consequence, the reduction in myelin thickness and the increase in degenerated myelin for groups ST and ST + HA in 30 day show that HA does not create a positive effect on axon regeneration in the short run, on the other hand, the reduction in myelin degenerated along with the increase of axon myelin thickness and axon cross section areas in groups ST and ST + HA in day 60 has shown that silicone tube and HA application creates a positive impact on myelination in the long run.
Deneysel peri ve epinöral nörorafi uygulanmi{dotless}ş rat modellerinde silikon tüp ve silikon tüp + hyaluronik asit uygulamasi{dotless}ni{dotless}n adezyon formasyonuna etkisi
Keywords: Sciatic nerve; Neurorrhaphy; Hyaluronic acid; Silicone tube; Rat